Contemporaneous theory in education - Vélez, María Gabriela Bravo; Sandoval, Elsa María Figueroa (International research journal of management, IT and social sciences, 2020)
The research contextually supports content focused on contemporary theories in the educational field and in which it presents the path of evolution in humanity, based on the learnings that have had to undergo it since the human being in its adaptation has allowed there to be a prospect to the educational advancement. The goal of research is to analyze the changes necessary for the creation and adaptation of learning to understand the development that learning has had in modern school. The bibliographic review and synthetic analytical method were used as a technique, to know contemporary theories and the influence they have on the learning-teaching process in education, it was obtained as a result that learning contemporary theories, fused to the modern school allow the expansion of knowledge by adapting techniques and strategies in students, in Ecuador has been involved the application of these, to develop new and diverse pedagogical processes, proposes training to teachers in new techniques to improve cognitive abilities.